Analysis of Rental Value of Shop Houses in Kecamatan Medan Petisah - Risuhendi R; Hilma Tamiami Fachrudin; Rina Bukit (Talenta Publisher, 2024)
This research aims to analyze the factors that influence the rental value of shophouses in Medan Petisah District, Medan City. The difference in shophouse rental prices is caused by increasingly expensive land prices, which are influenced by busy locations and the presence of new buildings. The Petisah area has experienced rapid development in recent years, causing a significant increase in land prices. This land issue is very important considering the increasing need for regional development. This research uses a market approach to determine the rental value of shophouses by analyzing the factors of building area, rights (certificates), building age, location, road width and parking area simultaneously and partially on the rental value of shophouses. This type of research is quantitative/associative/correlational with inferential statistical data analysis. The population of this study was all shophouses in Medan Petisah District, totaling 456 shophouses, with a sample of 82 shophouses. Data is processed using multiple regression analysis. The research results show that simultaneously, all independent variables have a significant effect on the rental value of shophouses. Partially, the variables of building area, rights (certificate), building age and parking area have a significant effect, while the variables of location and road width have no significant effect. Based on the regression coefficient value, the variables building area, rights (certificate), building age, and parking area have a positive and significant influence on shophouse rental values ​​in Medan Petisah District, Medan City